Hair removal with High Power Light-Emitting Diode (LED) – Evaluation by Infra-red Thermography: a pilot study (Research, Society and Development, 2021)
Introduction. Photoepilation use different light sources to remove unwanted body hair. The most common light sources used for permanent hair removal are diode lasers and intense pulsed light. Light assisted hair removal is based on the destruction of the follicular unit. The ability to remove hair without damaging the surrounding skin is based on selective photothermolysis, however, occurrence of side-effects such as pain and skin burning is reported for lasers and intense pulsed light. Objective. Here we investigate in a pilot study of a newly approved technology of High power LED with cooled probe, possible changes in skin temperature evaluated by infra-red thermography as well as acute and 24h sensitivity and pain by Visual Analogue Scale. Methods. Five participants with no restrictions of skin phototype were included in the pilot study. Skin Temperature was monitored before and after (30s, 5 and 10 min) after LED photoepilation, besides instant and 24h pain. Results. Nor significant increases on skin temperature and no 24h pain or any side-effects were reported. Acute pain during procedure ranged from 2 – 4 (VAS). Conclusion. High power LED with cooled probe seems to be a safe and efficient technology for photoepilation.